Variability of Cerebral Deep Venous System in Preterm and Term Neonates Evaluated on MR SWI Venography - Tortora, D.; Severino, M.; Malova, M.; Parodi, A.; Morana, G.; Ramenghi, L.A.; Rossi, A. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: The anatomy of the deep venous system is characterized by a great variability that might play an important role in the pathogenesis of brain lesions in the preterm brain. The aim of this study was to compare the anatomy of cerebral subependymal veins evaluated on SWI venography in 3 groups of neonates with normal brain MR imaging (very preterm [gestational age <32 weeks], moderate-to-late preterm [gestational age ≥32 to ≤37 weeks], and term neonates [gestational age >37 weeks]) and to evaluate the influence of preterm birth on development of subependymal veins.MATERIALS AND METHODS: SWI venographies of 84 very preterm, 31 moderate-to-late preterm, and 50 term neonates were retrospectively evaluated. Subependymal vein anatomy was classified into 6 different patterns: type 1 represented the classic pattern and types 2–6 were considered anatomic variants. A χ2 test was used to evaluate differences between the distributions of subependymal vein patterns.RESULTS: A significant difference (P = .011) was noticed between the 6 patterns based on gestational age. Type 1 was more frequent in term neonates (68%) than in both very preterm (41.7%) and moderate-to-late preterm neonates (56.5%). Anatomic variants were more common in very preterm neonates (66%) than in both moderate-to-late preterm (41%) and term neonates (36%). Interhemispheric asymmetry was more frequent in very preterm (59.5%) and moderate-to-late preterm neonates (51.6%) than in term neonates (34%; P = .017). Sex and monozygotic twin birth did not significantly affect the frequency of subependymal vein patterns (P = .0962).CONCLUSIONS: The deep venous system of the neonatal brain shows a large spectrum of anatomic variants with higher variability of subependymal vein anatomy in preterm than term neonates, likely related to the influence of the preterm birth and epigenetic factors on subependymal vein development.ASVanterior septal veinTSVthalamostriate veinDLVdirect lateral veinICVinternal cerebral veinSVsubependymal veins